KARAKTERISTIK SISTEM PERTANAMAN PEKARANGAN PASCAERUPSI TAHUN 2010 DI LERENG SELATAN GUNUNG MERAPI - , AGUS DWI PRASETIA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Research of âCharacteristics of Homegarden System in South Area of Mount Merapi After Eruption in 2010â aims to determine the characteristics and dynamics of the cropping pattern cultivation of seasonal crops in cropping systems based on the level of damage yard after eruptions. Retrieval of data using purposive sampling method at 30 yards in the village of Balerante during June- December 2013. Data obtained by the vertical projection of a tree as output horizontal from sexi-fs, field observations, interviews, diversity index types, important value index and similarity index . Volcanic eruptions affect the characteristics of the cropping pattern in heavily damaged, but did not affect the rate of moderate and light damage. It is evident from the calculation of diversity index of 1,18 on patterned heavily damaged trees along the border, the extent of damage was patterned alley cropping of 2,04 while the slightly damaged patterned random mixture of 2,35 and alley cropping. Overall 30 yard has a diversity index of 2,22. And the level of damage was minor resemblance is quite high at 0,59. INP shows sengon species dominance of 171,64 % at the level of heavy damage, this type of rehabilitation after eruption. The dynamics of the cultivation of annual crops include tobacco after eruptions Mount Merapi, gendruk, cassava, tales, Jipang, sugarcane, mustard planted in the dry season. Corn, ginger, chili planted in the rainy season, while kolonjono and elephant grass grown uncertain. Residents also cultivate bananas, papaya and barked continuously throughout the rainy season to dry.